Making motivation to work for lecturer in the universities by non-financial instruments now - Nguyễn Huyền Nga (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Making motivation to work for lecturer in the universities by non-financial instruments is meaningful activities in the short and long term to encourage lecturers improve their teaching quality and scientific research. To make better in making motivation to work for lecturers, this article focuses on analyzing the contents: role, essential, non-financial instruments, subjects, evaluation standards and offer solutions to make working motivation for lecturers by non-financial instruments in the universities now.